2014
DOI: 10.1111/mms.12177
|View full text |Cite
|
Sign up to set email alerts
|

False killer whales and fisheries interactions in Hawaiian waters: Evidence for sex bias and variation among populations and social groups

Abstract: We assessed scarring patterns as evidence of fisheries interactions for three populations of false killer whales in Hawai'i. Bycatch of the pelagic population in the tuna longline fishery exceeds their Potential Biological Removal level. Scarring was assessed by seven evaluators as consistent, possibly consistent, or not consistent with fisheries interactions, and average scores computed. Scores were highest for scarred main Hawaiian Island (MHI) false killer whales, followed by pelagic and Northwestern Hawaii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 22 publications
2
59
0
1
Order By: Relevance
“…Consistent with this general trend and the findings from our study, relatively high survival rates have also been shown in other T. aduncus populations (e.g., Reisinger and Karczmarski, 2010;Mansur et al, 2012;Webster et al, 2014). Our research provides an example for estimating sex-specific survival rates, which is especially important to determine for threatened populations (e.g., Baker et al, 2013) and for populations with sex-biased threats (e.g., Baird et al, 2015).…”
Section: Survival Rates Were High and Constantsupporting
confidence: 76%
See 1 more Smart Citation
“…Consistent with this general trend and the findings from our study, relatively high survival rates have also been shown in other T. aduncus populations (e.g., Reisinger and Karczmarski, 2010;Mansur et al, 2012;Webster et al, 2014). Our research provides an example for estimating sex-specific survival rates, which is especially important to determine for threatened populations (e.g., Baker et al, 2013) and for populations with sex-biased threats (e.g., Baird et al, 2015).…”
Section: Survival Rates Were High and Constantsupporting
confidence: 76%
“…Variability between sexes in demographic and population parameters can lead to conservation and management implications, as one sex may be more susceptible to threats than the other (e.g., Crespo et al, 1997;Van Dam et al, 2008;Schofield et al, 2013;Baird et al, 2015). For example, the wandering albatross (Diomedea exulans) exhibits sex-specific differences in foraging areas, which results in a sex-biased human induced mortality (Weimerskirch et al, 1997;Xavier and Croxall, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons causing such high proportions in the former species may be related to interactions with hook and line fisheries (Baird & Gorgone, ; Baird et al. ), as supported by dorsal fin disfigurement in other cetaceans caused by this type of fishery (e.g. Kiszka et al.…”
Section: Resultsmentioning
confidence: 99%
“…; Baird et al. ). Apparent vertebral column malformations included anomalies in the vertebra structure such as lateral curvature (scoliosis), or increased convexity or anterior concavity in the curvature (kyphosis or lordosis, respectively) of the vertebral column, as reviewed in Berghan & Visser ().…”
Section: Methodsmentioning
confidence: 98%
“…This suggests that fisheries interactions are occurring at a higher rate in one population, with a bias toward females, suggesting that fisheriesrelated mortality is likely to be disproportionate across these distinct populations (Baird et al, 2014). Thus, behavior is relevant for determining "distinct population segments" (DSP) and it has been argued that attempts to limit DSPs to purely "evolutionarily significant units" could compromise management efforts, since the use of demographic and behavioral data would be reduced (Pennock and Dimmick, 1997).…”
Section: Small Population Extinctionsmentioning
confidence: 99%